The application of feeding standard on weaned exotic pigs productivity - Djamuara Aritonang; M Silalahi; T Pasaribu; L.P Batubara; K Manihuruk; M Doloksaribu (Jurnal Ilmu Ternak dan Veteriner, 1997)
An experiment was conducted to evaluate the application of feeding standard on performances of weaned pigs . The experiment used 24 weaned exotic pigs aged 6 weeks averaged body weight 10 .7 kg for 14 weeks observation. Three different diets i .e . farmers formula (R), commercial diet (K) and standard diet according to NRC recommendation (S) were evaluated . The results showed that S diet on pigs produced better growth rate, feed consumption, feed conversion, cost and profit than other diets and K diet produced better feed conversion than R diet. Carry over effect of the treatments on the growth rate, feed conversion, cost and profit showed that pigs received S diet performed better than those received other diets . But,R diet gave the lowest cost and higher profit than Kdiet. These results concluded that S diet produced the best performance and profitable and produced carry over effect on pigs performances and can be recommended to farmers .   Keywords : Feeding standard, exotic pig